Potential Activity of Micafungin and Amphotericin B Co-Encapsulated in Nanoemulsion against Systemic Candida auris Infection in a Mice Model - Marena, Gabriel Davi [UNESP]; Carvalho, Gabriela Corrêa [UNESP]; Ruiz-Gaitán, Alba; Onisto, Giovana Scaramal [UNESP]; Bugalho, Beatriz Chiari Manzini [UNESP]; Genezini, Letícia Maria Valente [UNESP]; Santos, Maíra Oliveira Dos [UNESP]; Blanco, Ana Lígia [UNESP]; Chorilli, Marlus [UNESP]; Bauab, Tais Maria [UNESP] (MDPI, 2024)
The Candida auris species is a multidrug-resistant yeast capable of causing systemic and lethal infections. Its virulence and increase in outbreaks are a global concern, especially in hospitals where outbreaks are more recurrent. In many cases, monotherapy is not effective, and drug combinations are opted for. However, resistance to antifungals has increased over the years. In view of this, nanoemulsions (NEs) may represent a nanotechnology strategy in the development of new therapeutic alternatives. Therefore, this study developed a co-encapsulated nanoemulsion with amphotericin B (AmB) and micafungin (MICA) (NEMA) for the control of infections caused by C. auris. NEs were developed in previous studies. Briefly, the NEs were composed of a mixture of 10% sunflower oil and cholesterol as the oil phase (5:1), 10% Polyoxyethylene (20) cetyl ether (Brij® 58) and soy phosphatidylcholine as surfactant/co-surfactant (2:1), and 80% PBS as the aqueous phase. The in vivo assay used BALB/c mice weighing between 25 and 28 g that were immunosuppressed (CEUA/FCF/CAr n° 29/2021) and infected with Candida auris CDC B11903. The in vivo results show the surprising potentiate of the antifungal activity of the co-encapsulated drugs in NE, preventing yeast from causing infection in the lung and thymus. Biochemical assays showed a higher concentration of liver and kidney enzymes under treatment with AmB and MICAmB. In conclusion, this combination of drugs to combat the infection caused by C. auris can be considered an efficient therapeutic option, and nanoemulsions contribute to therapeutic potentiate, proving to be a promising new alternative.
Keywords: Candida auris; control of infection; in vivo assay; nanoemulsion; nanotechnology strategy